1989
DOI: 10.1111/j.1460-9568.1989.tb00372.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Characterization of Adrenocorticotrope Hormone (ACTH) Immunoreactive Fibres in the Mesencephalic Central Grey Substance of the Rat

Abstract: The fine structural localization of fibres immunoreactive for the adrenocorticotrope hormone (ACTH) was studied in the mesencephalic central grey substance (MCG) of the male Wistar rat. Light microscopically, varicose ACTH-immunoreactive fibres were found throughout the MCG in a dorsal, lateral and ventral, periventricular position. Electron microscopically, the immunoreactivity was most prominent in the direct vicinity of electron-dense secretory granules in axonal varicosities, and, although to a lower degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…However, in these studies, golgi complexes exhibited a close association with both dense core granules and vesicles, indicating that, at the ultrastructural level, POMC neurons might have the capacity to release both amino acid neurotransmitters and secretory peptides. Pre-embedding immunoelectron microscopy revealed that both small clear vesicles and dense core granules traffic to the axons and synapses of POMC neurons identified in the ARC (Matsumoto and Arai, 1978; Kiss and Williams, 1983; Buma et al, 1989). Other neurosecretory systems also have the capacity to release peptides from the soma or dendritic arbors (Morris and Pow, 1991; Huang and Neher, 1996; Ludwig et al, 2002), but these mechanisms appear to be cell-type specific (Ramamoorthy et al, 2011).…”
Section: Ultrastructural Organization Of Pomc Neuronsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in these studies, golgi complexes exhibited a close association with both dense core granules and vesicles, indicating that, at the ultrastructural level, POMC neurons might have the capacity to release both amino acid neurotransmitters and secretory peptides. Pre-embedding immunoelectron microscopy revealed that both small clear vesicles and dense core granules traffic to the axons and synapses of POMC neurons identified in the ARC (Matsumoto and Arai, 1978; Kiss and Williams, 1983; Buma et al, 1989). Other neurosecretory systems also have the capacity to release peptides from the soma or dendritic arbors (Morris and Pow, 1991; Huang and Neher, 1996; Ludwig et al, 2002), but these mechanisms appear to be cell-type specific (Ramamoorthy et al, 2011).…”
Section: Ultrastructural Organization Of Pomc Neuronsmentioning
confidence: 99%
“…Because fibers immunoreactive for POMC peptides co-ramify in target nuclei expressing either MCRs or opioid receptors, a simplistic scheme would suggest that POMC boutons and presynaptic terminals directly release neuropeptides onto other neurons expressing the appropriate receptors. However, neuroendocrine circuits such as the POMC system exhibit an interesting paradox: peptides released from POMC neurons can be detected at sites devoid of postsynaptic receptors (MacMillan et al, 1998), and at the ultrastructural level, neurons within the hypothalamus including presumptive POMC neurons appear to have the machinery to release peptides at non-synaptic sites as well (Leranth et al, 1980; Buma and Nieuwenhuys, 1988; Buma et al, 1989; van Lookeren Campagne et al, 1991). It has been suggested that circuits like the central POMC system may participate in both synaptic and volume transmission in the CNS (Golding, 1994; Agnati et al, 1995; van den Pol, 2012).…”
Section: Pomc Synapsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these are of hypothalamic origin and may contain peptides like luteinising hormone releasing hormone (LHRH), CRF or adreno-corticotropic hormone (ACTH) [12,14,122]. Others originate in the dorsal periaqueductal gray to descend towards the cervical and upper thoracic spinal cord, many of them contacting the perivascular spaces [22].…”
Section: Introductionmentioning
confidence: 99%
“…According to classically described mechanisms, boutons in presynaptic terminals should release neuropeptides onto other neurons expressing the appropriate receptors. Interestingly, peptides released from POMC neurons can be detected at sites devoid of postsynaptic receptors and at nonsynaptic sites as well [233][234][235][236]. Accordingly, POMC neurons may participate both in synaptic and volume transmission in the brain [237,238].…”
Section: Pomc Neuronsmentioning
confidence: 99%